2016
DOI: 10.1021/acs.nanolett.6b04659
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Mode Splitting in Photoluminescence of Individual Plasmonic Nanoparticles Strongly Coupled to Molecular Excitons

Abstract: Plasmon-exciton interactions are important for many prominent spectroscopic applications such as surface-enhanced Raman scattering, plasmon-mediated fluorescence, nanoscale lasing, and strong coupling. The case of strong coupling is analogous to quantum optical effects studied in solid state and atomic systems previously. In plasmonics, similar observations have been almost exclusively made in elastic scattering experiments; however, the interpretation of these experiments is often cumbersome. Here, we demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
290
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 195 publications
(317 citation statements)
references
References 71 publications
19
290
0
Order By: Relevance
“…Furthermore, TESC allows direct comparison of coupling parameters for individual emitters coupled to the same plasmonic cavity. This increases experimental flexibility enabling, for example, measurement of anticrossing curves through addressing different emitters with intrinsically varying cavity detuning δ instead of changing fundamental experimental parameters like laser power or temperature that can impact the underlying system properties . One can envision a broad range of new experiments based on this flexibility, such as TESC imaging in 2D Van der Waals materials, the investigation of randomly located single photon emitting defects in solid state systems that are difficult to probe with stationary plasmonic cavities despite their exceptional properties for quantum information and technology, and coupling of multiple single emitters for entanglement and superradiance .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, TESC allows direct comparison of coupling parameters for individual emitters coupled to the same plasmonic cavity. This increases experimental flexibility enabling, for example, measurement of anticrossing curves through addressing different emitters with intrinsically varying cavity detuning δ instead of changing fundamental experimental parameters like laser power or temperature that can impact the underlying system properties . One can envision a broad range of new experiments based on this flexibility, such as TESC imaging in 2D Van der Waals materials, the investigation of randomly located single photon emitting defects in solid state systems that are difficult to probe with stationary plasmonic cavities despite their exceptional properties for quantum information and technology, and coupling of multiple single emitters for entanglement and superradiance .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, plasmonic nano‐antenna cavities in the form of highly polarizable metallic nanostructures with dimensions down to just a few nanometers, which allow for deep sub‐diffraction limited mode volumes, have been broadly employed to generate hybrid quantum states of plasmons and emitters . The increased interaction rate facilitated by these nanoscopic cavity mode volumes have enabled strong coupling to both ensembles and single emitters at room temperature …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure b, we note that the spectral dip in the PL response coincides with that in the dark field spectra, but with upper polariton emission (ω + ) much less pronounced than the lower one (ω − ). We found that the splitting in the PL response is narrower than the dark field scattering counterparts, which appears to be in agreement with other works that investigated PL splitting in J‐aggregates coupled to silver nanoprisms . Our numerical calculations also yield a smaller splitting in the absorption cross section than in the scattering one (Figure S6, Supplementary Information).…”
Section: Resultsmentioning
confidence: 80%